2019
DOI: 10.1016/j.placenta.2019.06.379
|View full text |Cite
|
Sign up to set email alerts
|

Volume and vascularity: Using ultrasound to unlock the secrets of the first trimester placenta

Abstract: Fetal growth restriction (FGR) is a major cause of perinatal morbidity and mortality. Identifying which pregnancies are at risk of FGR facilitates enhanced surveillance and early delivery before fetal demise can ensue. However, existing risk stratification strategies yield an unacceptably low detection rate. A robust and reliable first trimester screening test for FGR would not only enable high-risk women to be appropriately monitored but would facilitate future trials for possible interventions to enhance fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Previously, 3-dimensional power Doppler imaging has been used to quantitatively analyze the placental microvascular architecture in unaffected and FGR fetuses; however, most of these studies were limited to early pregnancy and have not found wide clinical application. [13][14][15] Challenges may be related to equipment settings, requirements for experienced operators, and low reproducibility in the second and third trimesters. Magnetic resonance imaging (MRI) is a promising modality capable of measuring volumetric blood flow in the placenta, as it can quantify volumetric flow in the maternal and fetal sides separately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, 3-dimensional power Doppler imaging has been used to quantitatively analyze the placental microvascular architecture in unaffected and FGR fetuses; however, most of these studies were limited to early pregnancy and have not found wide clinical application. [13][14][15] Challenges may be related to equipment settings, requirements for experienced operators, and low reproducibility in the second and third trimesters. Magnetic resonance imaging (MRI) is a promising modality capable of measuring volumetric blood flow in the placenta, as it can quantify volumetric flow in the maternal and fetal sides separately.…”
mentioning
confidence: 99%
“…Previously, 3‐dimensional power Doppler imaging has been used to quantitatively analyze the placental microvascular architecture in unaffected and FGR fetuses; however, most of these studies were limited to early pregnancy and have not found wide clinical application 13–15 . Challenges may be related to equipment settings, requirements for experienced operators, and low reproducibility in the second and third trimesters.…”
mentioning
confidence: 99%
“…The seminal work of Grady [18] is the basis of a large number of publications with applications in biomedicine (fluorescent cell tracking [35], pap smear cells [10], tumor [40], [41], placenta [30], airway segmentation [34], [42], multimodal problems [3], [2]) and geophysical research [17]). It is also used in other algorithms (image superpixel segmentation [33] and deep learning techniques [28]).…”
Section: Related Workmentioning
confidence: 99%
“…[135][136][137] Uteroplacental vasculature can be identified towards the end of the first trimester, 138 and there have been recent striking developments in 3D ultrasonography to obtain human placental volumes and overlaying power Doppler ultrasound of the major vasculature. 139 Moreover, 3D ultrasound has been used to reveal placental volume and vascularity. [140][141][142][143][144] These approaches provide not only the opportunity for a screening test for growth restriction but also novel insight into how placental vasculature informs future health outcomes.…”
Section: Ultrasonographymentioning
confidence: 99%